2005
DOI: 10.1007/s00449-005-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and enzymatic adsorption model in a recirculation hollow-fibre bioreactor

Abstract: A general procedure has been developed to model the behaviour of enzymatic reactions in a membrane bioreactor. This procedure unifies the kinetics of the reaction and the adsorption of the enzyme or enzymatic complexes on the membrane, enabling the selection of the most appropriate kinetic model. The general procedure proposed has been particularized and applied to experimental results obtained with two enzymatic reactions carried out in a hollow-fibre reactor, enzymatic hydrolysis of lactose by beta-galactosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For the OES mode, with the substitution of ı 1 in Eq. (56), PT / F0 = 0.00512. Experimentally, it is found that the permeate flow augmented with F0 , and that in all the experiments made the value of PT / F0 remained practically constant and equal to 0.52%, as the model indicated.…”
Section: Oes Modementioning
confidence: 96%
See 1 more Smart Citation
“…For the OES mode, with the substitution of ı 1 in Eq. (56), PT / F0 = 0.00512. Experimentally, it is found that the permeate flow augmented with F0 , and that in all the experiments made the value of PT / F0 remained practically constant and equal to 0.52%, as the model indicated.…”
Section: Oes Modementioning
confidence: 96%
“…These operation modes are usually used, for example, to physically immobilize an enzyme in the shell [55][56][57], provided that the membrane is permeable to substrates and products. The driving force is the transmembrane pressure.…”
Section: Csfr Modementioning
confidence: 99%
“…Catalysts 2023, 13, x FOR PEER REVIEW 3 of 12 have all been used for lactose hydrolysis [3,27,28]. Membrane reactors have also been tested for this reaction and show lower enzymatic activity compared to the use of enzymes in batch reactors [29]. The aim of this work was to test a new method for immobilization of the enzyme βgalactosidase.…”
Section: Characterization Of Glass Fibersmentioning
confidence: 99%
“…Reactors such as fluidized bed, hollow fiber, plug flow, capillary bed and rolling membrane reactors have all been used for lactose hydrolysis [3,27,28]. Membrane reactors have also been tested for this reaction and show lower enzymatic activity compared to the use of enzymes in batch reactors [29].…”
Section: Introductionmentioning
confidence: 99%
“…Results from nonsteady state tests and a curve-matching method were used to estimate the maximum specific substrate utilization rate and half-velocity constant, and short term batch tests were conducted to estimate bacteria yield coefficient and the decay constant. A procedure that unifies the kinetics of reaction and adsorption of enzymes or enzymatic complexes was developed to model the enzymatic reactions in a MBR(Jurado et al, 2005). The model was applied to study the kinetics of enzymatic hydrolysis of lactose by beta-galactosidase and glucose-fructose isomerization by glucose isomerase in a hollow-fiber reactor.…”
mentioning
confidence: 99%